2004
DOI: 10.1093/nar/gkh201
|View full text |Cite
|
Sign up to set email alerts
|

The major 5' determinant in stop codon read-through involves two adjacent adenines

Abstract: The aim of this approach was to identify the major determinants, located at the 5' end of the stop codon, that modulate translational read-through in Saccharomyces cerevisiae. We developed a library of oligonucleotides degenerate at the six positions immediately upstream of the termination codon, cloned in the ADE2 reporter gene. Variations at these positions modulated translational read-through efficiency approximately 16-fold. The major effect was imposed by the two nucleotides immediately upstream of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
5
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 40 publications
5
69
5
1
Order By: Relevance
“…3A,B). Both the dependence upon the concentration of paromomycin and the dependence upon the flanking sequences are consistent with results in the literature (Bonetti et al 1995;Tork et al 2004;Salas-Marco and Bedwell 2005;Fan-Minogue and Bedwell 2008), providing further evidence for the sensitivity and versatility of the system for translational regulation. The paromomycinstimulated expression of the (CAA-TAA-CAA)-GFP is more than half that of the (CGA) 3 -GFP construct measured in the absence of paromomycin.…”
Section: Four Features Of Rna-id Contribute To Efficient Separation Osupporting
confidence: 88%
See 1 more Smart Citation
“…3A,B). Both the dependence upon the concentration of paromomycin and the dependence upon the flanking sequences are consistent with results in the literature (Bonetti et al 1995;Tork et al 2004;Salas-Marco and Bedwell 2005;Fan-Minogue and Bedwell 2008), providing further evidence for the sensitivity and versatility of the system for translational regulation. The paromomycinstimulated expression of the (CAA-TAA-CAA)-GFP is more than half that of the (CGA) 3 -GFP construct measured in the absence of paromomycin.…”
Section: Four Features Of Rna-id Contribute To Efficient Separation Osupporting
confidence: 88%
“…The efficiency of translation termination can be modulated by factors that increase misreading by the ribosome (SalasMarco and Bedwell 2005;Fan-Minogue and Bedwell 2008) as well as by the sequence context surrounding the stop codon (Bonetti et al 1995;Tork et al 2004). To determine whether we could observe paromomycin-induced misreading and context-dependent stop codon read-through with the RNA-ID system, we examined a set of GFP reporters bearing stop codons at amino acid 7 that differ in the codons that flank the stop codons.…”
Section: Four Features Of Rna-id Contribute To Efficient Separation Omentioning
confidence: 99%
“…Examination of stop codon context revealed that four out of the sup35-n mutations have an adenine at the À1 position, eight have an adenine in position À2 and four have an adenine in both positions (Table 2). It has been shown that the presence of two adenines immediately upstream of the stop codon facilitates translational readthrough in yeast (Tork et al 2004). Some of the sup35-n mutations are surrounded by flanking CAA codons, a context which was previously reported to cause high levels of suppression (Kopczynski et al 1992;Bonetti et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…tRNA decoding of a stop codon occurs more frequently when the stop codon is surrounded by a context that modifies the competition for stop codon recognition between a release factor and near-cognate tRNA (Salser 1969;Fluck and Epstein 1980;Engelberg-Kulka 1981). In Saccharomyces cerevisiae, both 59 and 39 sequences play a role in translation termination (Bonetti et al 1995;Namy et al 2001;Tork et al 2004). Several studies point to different elements that could be involved in the 59 effect in S. cerevisiae: (i) the tRNA located on the ribosomal P-site (Mottagui-Tabar and Isaksson 1998), (ii) the mRNA structure shape due to the nucleotide sequence at the P site that could alter decoding through distortion of the ribosome structure (Tork et al 2004), and (iii) the chemical property of the amino acid at the penultimate position.…”
mentioning
confidence: 99%
“…In Saccharomyces cerevisiae, both 59 and 39 sequences play a role in translation termination (Bonetti et al 1995;Namy et al 2001;Tork et al 2004). Several studies point to different elements that could be involved in the 59 effect in S. cerevisiae: (i) the tRNA located on the ribosomal P-site (Mottagui-Tabar and Isaksson 1998), (ii) the mRNA structure shape due to the nucleotide sequence at the P site that could alter decoding through distortion of the ribosome structure (Tork et al 2004), and (iii) the chemical property of the amino acid at the penultimate position. Previous analyses have shown that the nucleotides 39 of the stop have a predominant role on readthrough efficiency and that the 59 context effect is dependent on the 39 context (Skuzeski et al 1991;Bonetti et al 1995;Howard et al 1996;MottaguiTabar and Isaksson 1998;Cassan and Rousset 2001;Namy et al 2001).…”
mentioning
confidence: 99%